THE EFFECTS OF SMARTPHONE USAGE PREFERENCES OF CONSUMERS ON THE BUYİNG PROCESS UNDER THE SCOPE OF MOBİLE TECHNOLOGİES (Third Sector Social Economic Review, 2021)
Nowadays, the developments in internet and mobile device technologies allow both consumers and retailers to benefit more from the opportunities offered by mobile technologies with regards to marketing. In this context, consumer evaluations regarding mobile technologies, which have become one of the building blocks of multi-channel retailing, have come to the fore as a subject worth researching. The aim of this study is to examine the effects of usage precursor behaviours and attitudes towards the use of mobile technology on the stages of the buying decision process of consumers. In the research model developed based on the Technology Acceptance Model (TAM), the effects of perceived ease of use, perceived usefulness and attitude variables on each stage of the buying decision process were analyzed. The data required for the analyses were collected using a questionnaire that was designed online. As a result of the model test conducted using the structural equation with the data provided by 925 participants, the perceived ease of use and usefulness were found to be effective on the attitudes of consumers towards the use of mobile technology. In addition, it was determined that the consumers used their smartphones more intensively at the ‘information search’ and ‘evaluation of alternatives’ stages of the buying decision process.
Keywords: Mobile Marketing; Use of Mobile Technology; Buying Process